The Matchmaker Exchange API: Automating Patient Matching Through the Exchange of Structured Phenotypic and Genotypic Profiles - Buske, Orion J.; Schiettecatte, François; Hutton, Benjamin; Dumitriu, Sergiu; Misyura, Andriy; Huang, Lijia; Hartley, Taila; Girdea, Marta; Sobreira, Nara; Mungall, Chris; Brudno, Michael (Human mutation, 2015)
ABSTRACT Despite the increasing prevalence of clinical sequencing, the difficulty of identifying additional affected families is a key obstacle to solving many rare diseases. There may only be a handful of similar patients worldwide, and their data may be stored in diverse clinical and research databases. Computational methods are necessary to enable finding similar patients across the growing number of patient repositories and registries. We present the Matchmaker Exchange Application Programming Interface (MME API), a protocol and data format for exchanging phenotype and genotype profiles to enable matchmaking among patient databases, facilitate the identification of additional cohorts, and increase the rate with which rare diseases can be researched and diagnosed. We designed the API to be straightforward and flexible in order to simplify its adoption on a large number of data types and workflows. We also provide a public test data set, curated from the literature, to facilitate implementation of the API and development of new matching algorithms. The initial version of the API has been successfully implemented by three members of the Matchmaker Exchange and was immediately able to reproduce previously identified matches and generate several new leads currently being validated. The API is available at https://github.com/ga4gh/mme‐apis. The Matchmaker Exchange API defines a protocol and data format for exchanging phenotype and genotype profiles between patient databases, in order to facilitate the identification of additional cohorts and increase the rate with which rare diseases can be researched and diagnosed. The API is straightforward and flexible in order to simplify its adoption on a large number of data types and workflows.